A New Adapter Tuning of Large Language Model for Chinese Medical Named Entity Recognition - Lu Zhou; Yiheng Chen; Xinmin Li; Yanan Li; Ning Li; Xiting Wang; Rui Zhang (Applied Artificial Intelligence)
Named entity recognition (NER) is a crucial step in extracting medical information from Chinese text, and fine-tuning large language models (LLMs) for this task is an effective approach. However, full parameter fine-tuning can potentially damage the model’s original parameters, resulting in catastrophic forgetting. To overcome this challenge, we introduce a novel adapter-based fine-tuning approach. Our adapter is integrated into the first and last transformers of the LLM, operating in parallel to the feed-forward network (FFN), following multi-head attention. It mirrors the FFN’s structure and uses the FFN’s weights for initializing. Additionally, to further enhance performance, we incorporate prefix embeddings into the first and last transformers. Our experiments on the Chinese medical NER benchmark demonstrate that our adapter, combined with prefix embeddings, achieves the highest F1-score of 65.90%, surpassing prompt templates (21.99%), in-context learning (18.65%), P-tuning (63.03%), and the benchmark for the Chinese medical NER task (62.40%). These results indicate that our adapter effectively fine-tunes the LLM for Chinese medical NER while preserving the original parameters.